2020
DOI: 10.1002/mma.6431
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic analysis of anisotropic half space containing an elliptical inclusion under SH waves

Abstract: Based on the methods of complex function, conformal mapping, and multipolar coordinate system, dynamic response of an elliptical inclusion embedded in an anisotropic half space is investigated. In order to find the solution of SH waves, the governing equation is transferred into its normalized form. Then, the scattering wave induced by the inclusion and the standing wave in the inclusion is deduced. Different incident wave angles and the corresponding anisotropy of the half space are considered to obtain the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The displacement and stress fields were determined by the Green's function method and conformal mapping and the influence factors for the spatial distribution of DSCF were analyzed. Jiang et al (2020) employed the complex function method to obtain the DSCF around an elliptical inclusion in the anisotropic half-space. The numerical results indicated that the wave number, incidence angle, and anisotropic parameters significantly influenced the spatial distribution of DSCF.…”
Section: Introductionmentioning
confidence: 99%
“…The displacement and stress fields were determined by the Green's function method and conformal mapping and the influence factors for the spatial distribution of DSCF were analyzed. Jiang et al (2020) employed the complex function method to obtain the DSCF around an elliptical inclusion in the anisotropic half-space. The numerical results indicated that the wave number, incidence angle, and anisotropic parameters significantly influenced the spatial distribution of DSCF.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the discontinuity of structure, inclusions often exist in different objects, such as underground structure in the stratum, impurities in materials, and so on. Scattering and dynamic stress concentration will occur around inclusions when subjected to stress wave, 1,2 which may cause the structural failure of inclusions. Thus, dynamic response of a medium with inclusions embedded in elastic waves should be considered seriously.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with circular tunnels, elliptical tunnels are more challenging to study as the study involves elliptical boundary and multi‐elliptical coordinate system transformation problems. While the utilization of complex functions and the sophisticated application of multipolar coordinate techniques have made it convenient to deal with the scattering problems of cylindrical structures, 14 but it is still difficult to deal with the scattering problem of elliptical cylinders using these methods 15 . Mathieu functions are currently an effective method for solving elliptic boundary value problems 16–18 .…”
Section: Introductionmentioning
confidence: 99%
“…While the utilization of complex functions and the sophisticated application of multipolar coordinate techniques have made it convenient to deal with the scattering problems of cylindrical structures, 14 but it is still difficult to deal with the scattering problem of elliptical cylinders using these methods. 15 Mathieu functions are currently an effective method for solving elliptic boundary value problems. [16][17][18] With the maturity of numerical computation and computing power, it has been widely used in physics, electromagnetism, and microwave technology.…”
mentioning
confidence: 99%